Micro-deformation characterization of electronic packaging materials and assemblies - Sun, Yao Feng (2010)
The continuing miniaturization of microelectronic assemblies and devices requires experimental micro-deformation analysis technique for material characterization and structure reliability analysis. This work investigates both theoretical aspects and practical applications of digital image correlation techniques for in-plane micro- and non-scale deformation characterization of electronic packaging materials and assemblies.